Heritability of ischaemic stroke in women compared with men: a genetic epidemiological study. - Touzé, E; Rothwell, P (2007)
BACKGROUND: Ischaemic stroke is partly heritable. However, although the genetic and non-genetic factors responsible could be sex-specific, interactions between the sex of the parent affected and the sex of the proband or affected siblings are unknown. We sought to assess the relation between the sex and phenotype of affected probands and the sex of affected first-degree relatives. METHODS: We determined the prevalence of history of stroke in the mother, father, and other first-degree relatives in female and male probands with ischaemic stroke or transient ischaemic attack in the population-based Oxford Vascular Study (OXVASC). We validated our findings using unpublished individual patient data from two independent Oxford studies. FINDINGS: In OXVASC, detailed family history was available in 806 (93%) probands. Female probands were more likely than males to have at least one affected first-degree relative (146/423 vs 104/383; OR 1.4, 95% CI 1.1-2.0, p=0.02) due entirely to an excess of affected female relatives in female probands (female relative vs male relative OR=1.7, 1.3-2.4, p=0.0004; female only vs male only OR=2.1, 1.4-3.1, p=0.0001). Maternal stroke was more common than paternal stroke in female probands (OR=1.8, 1.2-2.7, p=0.001) but not in males (OR=1.1, 0.7-1.7, p=0.38), and female probands were more likely than males to have an affected sister (OR=3.1, 1.5-6.7, p=0.004) but not an affected brother (OR=1.1, 0.6-2.1, p=0.80). Ages at first stroke were also correlated within families among affected females (r=0.36, p=0.004) but not among affected males, such that the excess of affected female relatives of female probands was greatest when the difference in age at first stroke was less than 5 years (OR=3.7, 1.6-8.6, p=0.0007) and fell as the age difference increased (p for trend=0.004). These findings were independent of traditional risk factors and stroke subtype. Data from the other Oxford studies confirmed the excess maternal history of stroke in female probands (OR=2.3, 1.5-3.8, p<0.00001) and the lack in males (OR=1.0, 0.7-1.4, p=0.58). INTERPRETATION: Heritability of ischaemic stroke is greater in women than in men, with an excess of affected mothers and affected sisters in female probands independent of traditional vascular risk factors, which could be explained by sex-specific genetic, epigenetic, or non-genetic mechanisms.